Student Tolerance Attitudes in Islamic Boarding Schools - Hilmansah, Deden; Komarudin, Komarudin; Al Ayyubi, Ibnu Imam; Prayetno, Eko; Yumna, Hanin (Southeast Asian Journal of Islamic Education, 2024)
This study aims to describe the tolerance attitudes of students in Islamic boarding schools, focusing on three aspects: peace, respect for differences and individuals, and awareness. The research method is descriptive quantitative, utilizing a Likert scale questionnaire for data collection. Results indicate that 48% of students exhibit very high tolerance in the peace aspect, while 52% show high tolerance. Regarding respect for differences and individuals, 55% of students demonstrate very high tolerance and 45% show high tolerance. In the awareness aspect, 59% of students display very high tolerance, and 41% show high tolerance. Overall, 60% of students have a very high tolerance attitude, and 40% show a high tolerance attitude. These findings highlight that Islamic boarding schools foster an environment conducive to developing academically proficient students with strong religious and tolerant attitudes. The implication is that Islamic boarding schools play a vital role in shaping students who are not only academically capable but also possess strong religious and tolerant attitudes. This suggests that an educational approach integrating Islamic spiritual values with general knowledge can be an effective model for fostering a more inclusive and socially aware generation. Furthermore, this model demonstrates the potential of education to serve as a bridge for understanding and respecting cultural and religious diversity, equipping students with the skills and values needed to contribute positively to a pluralistic society.